Emphasizing Multicultural and Anti-racist Pedagogies as One Aspect of Decolonizing Education - Rawia Azzahrawi (Canadian Society for Studies in Education, 2020)
Learning diverse languages, cultures, and communicating with different nationalities within a schools' environment helps students appreciate the multi-ethnic nature of our world. They also help them realize the inherent values, beliefs, morals, and principles of the cultures they meet. In Canadian history, multiculturalism is a vital component in its existence. According to the World Migration Report (2017), Canada is considered one of the leading countries in international migrants (Report, 2017, p. 18). These various cultures and ethnicities deserve special attention; recognizing their influences, impacts, and inspirations on the cultural life of communities are critical. This paper discusses how multicultural and anti-racist pedagogies can be used as one of the elements of decolonizing education. Furthermore, the paper studies the role of colonialism in today's education and suggests several recommendations in order to prevent racism in the educational system. Incorporating members with diverse cultural practices, beliefs, and contributions are critical. Supporting them to live, work, and communicate with other groups in society may ultimately assist in developing more cohesive and productive communities.